Challenges and Opportunities of Low-Carbon Rice Production Systems in Bangladesh - Ahmed, Sharif; Bhandari, Humnath; Kumar, Virender (International Rice Research Institute, 2025)
Rice covers 11% of the world's arable land and is responsible for approximately 1.5% of global anthropogenic GHG emissions and around 10-12% of total agricultural emissions. Bangladesh is one of the most rice-dependent countries (cultivates ~ 75 of its arable land) in the world, facing the dual challenge of ensuring food security while minimizing environmental impacts. The country has extensive rice cultivation covering approximately 11.5 million hectares (production ~39 million tons), significantly contributing to greenhouse gas emissions. In Bangladesh, rice cultivation is responsible for approximately 18-22% of the total anthropogenic GHG emissions, where the total agricultural emission (including livestock) is around 28-30%. In the agricultural sector, methane (CH₄) is the major contributor to the GHG emissions, where rice contributes around 62%. The contribution of rice to agricultural N2O emissions is around 11-13%.